Stuffocation : why we've had enough of stuff and need experience more than ever - Wallman, James (Spiegel & Grau, 2015)
"For many of us, our possessions and the lifestyle that goes along with them are causing more stress than happiness--otherwise known as "keeping up with the Joneses" or what Alain de Botton calls "status anxiety." But James Wallman argues that we are approaching a tipping point with regard to materialism. People are turning away from the endless drive to consume in favor of a simpler, more streamlined way of living. The shift is already underway: influential millennials favor Zipcars over owning cars, share music on Spotify, and read e-books rather than accumulating a bulky physical library. Wallman blames our obsession with "stuff" on the original Mad Men who first "created desire" through advertising, with unintended consequences that ripple through our lives today. He interviews anthropologists studying the 21st century clutter crisis, consults with scientists who have linked "stuffocation" to rising cortisol levels and declining psychological wellbeing, and introduces us to the innovators who are already choosing "experience" over "stuff." A paradigm-shifting look at how and why we consume, and an inspiring manifesto for living more with less"--